Combinatorial Optimization and Applications 8th International Conference, COCOA 2014, Wailea, Maui, HI, USA, December 19-21, 2014, Proceedings - Zhang, Zhao.; Wu, Lidong; Xu, Wen.; Du, Ding-Zhu.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 8th International Conference on Combinatorial Optimization and Applications, COCOA 2014, held on the island of Maui, Hawaii, USA, in December 2014. The 56 full papers included in the book were carefully reviewed and selected from 133 submissions. Topics covered include classic combinatorial optimization; geometric optimization; network optimization; optimization in graphs; applied optimization; CSoNet; and complexity, cryptography, and games.
An Exact Algorithm for Non-preemptive Peak Demand Job Scheduling -- An Asymptotic Competitive Scheme for Online Bin Packing -- Randomized Online Algorithms for Set Cover Leasing Problems -- Optimizing Squares Covering a Set of Points -- Algorithms for Fair Partitioning of Convex Polygons -- A Quasi-polynomial Time Approximation Scheme for Euclidean CVRPTW -- On-Line Strategies for Evacuating from a Convex Region in the Plane -- Rectilinear Duals Using Monotone Staircase Polygons -- Optimal Strategy for Walking in Streets with Minimum Number of Turns for a Simple Robot -- Guarding Monotone Art Galleries with Sliding Cameras in Linear Time -- Information Gathering in Ad-Hoc Radio Networks with Tree Topology -- Improved Algorithms for Computing Minmax Regret 1-Sink and 2-Sink on Path Network -- Approximate Aggregation for Tracking Quantiles in Wireless Sensor Networks -- Interference-Free k-barrier Coverage in Wireless Sensor Networks -- Performance Analysis and Improvement for the Construction of MCDS Problem in 3D Space -- A Practical Greedy Approximation for the Directed Steiner Tree Problem -- Spanning Properties of Theta-Theta Graphs -- A Bicriteria Approximation Algorithm for DVRP with Time Windows -- Data-Oblivious Graph Algorithms in Outsourced External Memory -- A Dichotomy for Upper Domination in Monogenic Classes -- Algorithms for the Maximum Weight Connected k-Induced Subgraph Problem -- Algorithms for Cut Problems on Trees -- The Minimum Vulnerability Problem on Graphs -- The List Coloring Reconfiguration Problem for Bounded Pathwidth Graphs -- Two Paths Location of a Tree with Positive or Negative Weights -- Approximation Algorithms for Optimization Problems in Random Power-Law Graphs -- A Comparison Between the Zero Forcing Number and the Strong Metric Dimension of Graphs -- Optimal Trees for Minimizing Average Individual Updating Cost -- Cascading Critical Nodes Detection with Load Redistribution in Complex Systems -- The Power of Rejection in Online Bottleneck Matching -- The Generalized 3-Edge-Connectivity of Lexicographic Product Graphs -- Integer Programming Methods for Special College Admissions Problems -- On the Width of Ordered Binary Decision Diagrams -- Tight Analysis of Priority Queuing for Egress Traffic -- Optimally Bracing Grid Frameworks with Holes -- Top-K Query Retrieval of Combinations with Sum-of-Subsets Ranking -- Efficient Group Testing Algorithms with a Constrained Number of Positive Responses -- Maximizing Revenues for On-Line Dial-a-Ride -- Global Internet Connectedness: 2002–2011 -- Optimal Containment of Misinformation in Social Media: A Scenario-Based Approach -- Multivariate Heavy Tails in Complex Networks -- Mixed Degree-Degree Correlations in Directed Social Networks -- Social and Economic Network Formation: A Dynamic Model -- A Region Growing Algorithm for Detecting Critical Nodes -- A Fast Greedy Algorithm for the Critical Node Detection Problem -- Integer Programming Formulations for Minimum Spanning Forests and Connected Components in Sparse Graphs -- Complexity, Cryptography and Game -- On the Parameterized Complexity of Dynamic Problems with Connectivity Constraints -- Parameterized and Subexponential-Time Complexity of Satisfiability Problems and Applications -- Kolmogorov Structure Functions for Automatic Complexity in Computational Statistics -- Improved Even Order Magic Square Construction Algorithms and Their Applications -- The Complexity of the Positive Semidefinite Zero Forcing -- A Potential Reduction Algorithm for Ergodic Two-Person Zero-Sum Limiting Average Payoff Stochastic Games -- The Popular Matching and Condensation Problems Under Matroid Constraints -- Incremental Computation of Pseudo-Inverse of Laplacian -- Optimal Tracking of Multiple Targets Using UAVs -- Approximation Algorithm for the Minimum Connected k-Path Vertex Cover Problem.
Keywords: Algorithms; Computer science—Mathematics.; Numerical analysis; Computer communication systems; Computer graphics; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Numeric Computing; Algorithms; Computer Communication Networks; Computer Graphics